2001
DOI: 10.1366/0003702011952767
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR Microscopic Base Imaging System: Applications for Chemical Analysis of Zn and Ni Atmospheric Corrosion

Abstract: The possible use of an FT-IR imaging system for surface studies of atmospheric corrosion products on zinc and nickel samples has been explored. Samples have been exposed in an urban site located at Rouen in France. Corrosion products, detected by means of energy-dispersive spectrometry/X-ray diffraction (EDS/XRD) and FT-IR spectroscopy, are mainly Zn4CO3(OH)6·H2O, ZnSO3·nH2O, Zn4SO4(OH)6·nH2O, and NiSO4·xH2O. IR microspectroscopy and mapping techniques allow the observation of the heterogeneous distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…IR Spectroscopy is a significant method to analyze the accomplishment of the solid-state reaction and investigate the deformation existence in the spinel structure due to foreign ions or cationic distribution [56,57]. In our experimental results of FT-IR spectra, all the samples exhibit two prominent frequency bands at 370 and 580 cm −1 , measured in the wavelength range of 1000–350 nm, displaying pure spinel phase.…”
Section: Resultsmentioning
confidence: 83%
“…IR Spectroscopy is a significant method to analyze the accomplishment of the solid-state reaction and investigate the deformation existence in the spinel structure due to foreign ions or cationic distribution [56,57]. In our experimental results of FT-IR spectra, all the samples exhibit two prominent frequency bands at 370 and 580 cm −1 , measured in the wavelength range of 1000–350 nm, displaying pure spinel phase.…”
Section: Resultsmentioning
confidence: 83%
“…FTIR is very useful to perform the characterization of corroded surface as it was demonstrated in previous works [9]. Contrary to X-ray analysis, both crystalline and amorphous corrosion products can be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…6. Samples of hydrozincite, Zn 5 CO 3 2 OH 6 , have been measured by Lefez et al 17 and shown also to have absorbance at 1495 and 1555 cm 1 . Figure 7 shows XPS spectra at the surface and at different depths into the surface of a carbon-dioxide-plasma-treated zinc sample.…”
Section: Carbon Dioxide Plasma Treatmentmentioning
confidence: 99%